NaOCl produced by electrolysis of natural seawater as a potential method to control marine red-tide dinoflagellates - Jeong, Hae Jin; Kim, Heung Rak; Kim, Kwang Il; Kim, Kwang Young; Park, Kwan Ha; Kim, Seong Taek; Yoo, Yeong Du; Song, Jae Yoon; Kim, Jae Seong; Seong, Kyeong Ah; Yih, Won Ho; Pae, Se Jin; et al. (Phycologia (Oxford), 2002)
As part of the development of a method to control the outbreak and persistence of red tides using sodium hypochlorite (NaOCl), we investigated the effect of NaOCl on the survival of red-tide dinoflagellates, diatoms, heterotrophic protists, planktonic crustaceans, fin-fish, shellfish, and macroalgae. Because NaOCl introduced into natural waters would be subject to dilution, as well as breakdown in sunlight to NaCl, the survival of organisms was determined after 10 min exposure and 1 h exposure to NaOCl, and again after transfer to fresh seawater for 6 or 24 h. The lethal total residual chlorine (TRC) concentration that killed 50% of the test organisms (LC 50 ) for the red-tide dinoflagellates Gymnodinium catenatum , Cochlodinium polykrikoides , Akashiwo sanguinea , Lingulodinium polyedrum , Prorocentrum micans , Alexandrium affine , and Gymnodinium impudicum ranged from 57 to 157 ppb for 10 min exposure and from 30 to 106 ppb for 1 h exposure. Complete mortality of all red-tide species occurred at TRC concentrations of ~ 500 ppb. The LC 50 of the diatoms Skeletonema costatum and Thalassiosira rotula , 3083-3383 ppb for 10 min exposure and 3128-3433 ppb for 1 h exposure, were much higher than for red-tide dinoflagellates. But the LC 50 s of the heterotrophic dinoflagellates Polykrikos kofoidii and Oxyrrhis marina were similar to those of red-tide dinoflagellates. The ciliate Strombidinopsis sp. had LC 50 s of 306 ppb for 10 min exposure and 119 ppb for 1 h exposure, which are higher than those for dinoflagellates. The LC 50 s of the calanoid copepods Acarlia spp. and Pseudodiaptomus sp. were 1397-1493 ppb for 10 min exposure and 744-987 ppb for 1 h exposure, and those for larvae of the brine shrimp Artemia franciscana were 4905 ppb for 10 m exposure and 2814 ppb for 1 h exposure. The LC 50 s of juvenile gray mullet Mugil cephalus and juvenile black rockfish Sebastes schlegeli were 1234-1883 ppb for 10 min exposure and 1234-1440 ppb for 1 h exposure, whereas those of adult Manila clam Ruditapes philippinarum and spat of the abalone Nordotis discus were> 20,000 ppb. The LC 50 s of the macroalgae Griffithsia japonica (Rhodophyta) and Ulva pertusa (Chlorophyta) were 1519-12,365 ppb for 10 min exposure and 1085-12,558 ppb for 1 h exposure. The present study therefore suggests that, if NaOCl is introduced into waters containing red-tide organisms at TRC concentrations of 300-500 ppb for 10 min exposure and 200-400 ppb for 1 h exposure, red tides can be effectively controlled without serious harmful effects on other marine organisms, except heterotrophic dinoflagellates.